Cost analysis of bluetongue virus serotype 8 surveillance and vaccination programmes in Austria from 2005 to 2013. Issue 2 (November 2015) - Pinior, Beate; Lebl, Karin; Firth, Clair; Rubel, Franz; Fuchs, Reinhard; Stockreiter, Simon; Loitsch, Angelika; Köfer, Josef
Highlights: Costs of bluetongue (BT) control programmes before, during and after the outbreak in Austria in 2008 are analysed. A spatial investigation of BTV programme costs in political districts in Austria is provided. The total net cost of BTV-8 surveillance and vaccination in Austria between 2005 and 2013 was €22.8 million. Simple parameters to predict future costs are suggested. In-kind contributions need to be visible to decision makers. Abstract: This study was designed to evaluate the costs between 2005 and 2013 of the national bluetongue virus (BTV) surveillance and vaccination programmes before, during and after the BTV serotype 8 (BTV-8) outbreak in Austria commencing in 2008. In addition to an assessment of the temporal development of costs, a spatial cost analysis was performed. Within the context of this study, the term 'costs' refers to actual financial expenditure and imputed monetary costs for contributions in-kind. Costs were financed directly by the private–public sectors, by the European Commission (EC), and (in-kind) by responsible national institutions and individuals (e.g. blood sampling by veterinarians). The total net cost of the BTV-8 surveillance and vaccination programmes arising from the outbreak amounted to €22.8 million (0.86% of the national agricultural Gross Value Added), of which 32% was allocated to surveillance and 68% to the vaccination programme. Of the total programme costs, the EC supplied €4.9 million, while the remaining costs (€18 million) were directly financed from national resources. Of the latter, €14.5 million was classed as public costs, including €2 million contributions in-kind, and €3.4 million as private costs. The assessment of the costs revealed heterogeneous temporal and spatial distributions. The methodology of this analysis might assist decision makers in calculating costs for other surveillance and intervention programmes. The assessment of contributions in-kind is of importance to public authorities as it increases visibility of the available resources and shows how they have been employed. This study also demonstrates the importance of tracking changing costs per payer over time.